GEOCHEMISTRY OF SOUTH AFRICAN ON- AND OFF-CRATON, GROUP I AND GROUP II KIMBERLITES: PETROGENESIS AND SOURCE REGION EVOLUTION - Becker M.; Le Roex A.P. (My University, 2006)
Bulk-rock geochemical compositions of hypabyssal kimberlites, emplaced through the Archaean Kaapvaal craton and Proterozoic Namaqua-Natal belt, are used to estimate close-to-primary magma compositions of Group I kimberlites (Mg-number = 0·82-0·87; ~22-28 wt % MgO; ~21-30 wt % SiO2; ~10-17 wt % CaO; ~0·2-1·7 wt % K2O) and Group II kimberlites (Mg-number = 0·86-0·89; ~23-29 wt % MgO; ~28-36 wt% SiO2; 8-13 wt % CaO; ~1·6-4·6 wt % K2O). Group I kimberlites are distinguished from Group II by their lower Ba/Nb (<12), Th/Nb (<1·1) and La/Nb (<1·1) but higher Ce/Pb (>22) ratios. The distinct rare earth element patterns of the two types of kimberlites indicate a more highly metasomatized source for Group II kimberlites, with more residual clinopyroxene and less residual garnet. The similarity of Sr and Nd isotope ratios and diagnostic trace element ratios (Ce/Pb, Nb/U, La/Nb, Ba/Nb, Th/Nb) of Group I kimberlites to ocean island basalts (OIB), but more refractory Mg-numbers and Ni contents, are consistent with derivation of Group I kimberlites from subcontinental lithospheric mantle (SCLM) that has been enriched by OIB-like melts or fluids. Source enrichment ages and plate reconstructions support a direct association of these melts or fluids with Mesozoic upwelling beneath southern Africa of a mantle plume(s), at present located beneath the southern South Atlantic Ocean. In contrast, the geochemical characteristics of both on- and off-craton Group II kimberlites show strong similarity to calc-alkaline magmas, particularly in their Nb and Ta depletion and Pb enrichment. It is suggested that Group II kimberlites are derived from both Archaean and Proterozoic lithospheric mantle source regions metasomatized by melts or fluids associated with ancient subduction events, unrelated to mantle plume upwelling. The upwelling of mantle plumes beneath southern Africa during the Mesozoic, at the time of Gondwana break-up, may have acted as a heat source for partial melting of the SCLM and the generation of both Group I and Group II kimberlite magmas. © 2006 Oxford University Press.
Keywords: GEOCHEMISTRY; KIMBERLITE; MANTLE PLUMES; PETROGENESIS; SOUTH AFRICA; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой